Perlindungan Debitur dalam Pembiayaan Melalui Jaminan Fidusia: Analisis Hukum Ekonomi Syariah - Pratama, Alandra; Sunaryo; Zazili, Ahmad; Rohaini; Kasmawati (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2025)
The use of fiduciary guarantees in Sharia-based consumer financing raises legal issues concerning debtor protection, particularly regarding justice, legal certainty, and execution mechanisms. Juridically, fiduciary guarantees function as instruments for creditor protection; therefore, debtor protection does not arise from the guarantee itself but from legal regulations and limitations on its execution. This study aims to analyze debtor legal protection in Sharia-based consumer financing utilizing fiduciary guarantees from the perspective of Indonesian positive law and Islamic economic law. This research employs a normative legal research method with statutory and conceptual approaches. The findings indicate that the regulation of fiduciary guarantees has not fully ensured debtor protection, especially in execution practices. From the perspective of Islamic economic law, such practices potentially contradict the principles of justice, the prohibition of oppression (ẓulm), and the objectives of maqāṣid al-sharī‘ah, particularly the protection of property (ḥifẓ al-māl). Therefore, the application of fiduciary guarantees in Sharia financing must be harmonized with the principles of rahn, the nature of Sharia contracts, as well as DSN-MUI fatwas and Sharia financial regulations issued by the Financial Services Authority.